2017
DOI: 10.1097/md.0000000000006189
|View full text |Cite
|
Sign up to set email alerts
|

Identifying multiple myeloma patients using data from the French health insurance databases

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
(23 reference statements)
2
16
0
Order By: Relevance
“…European registries found that CML annual incidence is around 1.1/100 000 , but worldwide data show many differences between countries: from 0.4/100 000 in some non‐Western countries to 1.75/100 000 in the USA . When considering CML LTD only, we identified only 50 patients, corresponding to an annual crude incidence of 0.69/100 000; this is significantly lower than incidence rates reported in cancer registries, and we could not base our selection upon such a method; however, these data are consistent with the already reported low declaration rate of LTD hematologic malignancies (around 50%) . LTD is inconstantly declared in France and of 690 patients with at least one CML TKI dispensing in our study, 91 had no LTD at all, and 137 had no cancer LTD. Thirty‐four patients have been excluded because they had CML code at least 9 months prior to F‐TKI; they must have been prevalent CML patients exiting a clinical trial (TKI having been previously refunded by the pharmaceutical firm), having had a sustained response without treatment, having moved to Midi‐Pyrénées, or having changed their insurance system while being treated by TKI.…”
Section: Discussionsupporting
confidence: 58%
“…European registries found that CML annual incidence is around 1.1/100 000 , but worldwide data show many differences between countries: from 0.4/100 000 in some non‐Western countries to 1.75/100 000 in the USA . When considering CML LTD only, we identified only 50 patients, corresponding to an annual crude incidence of 0.69/100 000; this is significantly lower than incidence rates reported in cancer registries, and we could not base our selection upon such a method; however, these data are consistent with the already reported low declaration rate of LTD hematologic malignancies (around 50%) . LTD is inconstantly declared in France and of 690 patients with at least one CML TKI dispensing in our study, 91 had no LTD at all, and 137 had no cancer LTD. Thirty‐four patients have been excluded because they had CML code at least 9 months prior to F‐TKI; they must have been prevalent CML patients exiting a clinical trial (TKI having been previously refunded by the pharmaceutical firm), having had a sustained response without treatment, having moved to Midi‐Pyrénées, or having changed their insurance system while being treated by TKI.…”
Section: Discussionsupporting
confidence: 58%
“…Multiple myeloma patients were identified through hospital diagnosis or long‐term conditions, using ICD10 code for multiple myeloma (C90). The validity of this algorithm has been demonstrated elsewhere, with a sensitivity of 90%, a specificity of 100% (positive predictive value 60%, negative predictive value 100%) …”
Section: Methodsmentioning
confidence: 99%
“…The validity of this algorithm has been demonstrated elsewhere, with a sensitivity of 90%, a specificity of 100% (positive predictive value 60%, negative predictive value 100%). 11 Those with at least 1 dispensing record for lenalidomide, thalidomide, bortezomib, melphalan, doxorubicin, cyclophosphamide or bendamustine were selected.…”
Section: Patients Selectionmentioning
confidence: 99%
“…Conversely we did not have the means to determine those patients with myeloma and for whom this information was not present in the database. A recent publication by Palmaro et al suggests that the diagnostic codes present in the PMSI database can be used with a good specificity to identify incident cases of myeloma [ 9 ].…”
Section: Methodsmentioning
confidence: 99%